Pemoderasi Teknologi Informasi pada Pengaruh Dimensi Manajemen Mutu Terpadu terhadap Kinerja Organisasi (Studi pada Organisasi Manufaktur Bersertifikat Seri ISO 9000 di Jawa Timur) - Hidayat, Anang (Jurnal Aplikasi Manajemen, 2009)
The objectivity of this study is to test and analyze information technology as variable which moderate the effects of total quality management dimension toward organization performance. This research used moderated structural equation modeling to evaluate the moderating information technology on the effect of total quality management toward organization performance. Based on data analysis result, firstly, total quality management positively affected on organization performance. Second, the interaction between total quality management and information technology is positive significant impact on organization performance, so it can be concluded that information technology was variable which moderate the effects of total quality management towards organization performance. Third, the personnel’s involvement was one of the total quality management dimensioned that had biggest influence on organization performance. This finding represented that certification of ISO 9000 series on manufacturing industrial had brought the personnel’s involvement in high participation and contribution level on organization performance. Fourth, the effect of supplier relationship towards organization performance was the lowest compared to other total quality managements. Fifth, the biggest moderating of information technology was in the effect of leadership dimension towards organization performance. This condition showed that utilization of information technology was more used for top management interest in high organization performance achievement. It was assumed that the handling of information technology in general was in intermediate to high level in organization structure. Sixth, the feeblest moderating of information technology was in the influence of supplier connection dimension towards organization performance. It showed that utilization of information technology was not functioned for making the connection to supplier in long term way.Keywords: Total Quality Management, Information Technology, Moderating Impact